Mechanics of composite materials - Kaw, Autar K. (Mechanical engineering series (Boca Raton, Fla.), 2005)
The book begins with a question-and-answer style introduction to composite materials, including updated material on new applications. The remainder of the book discusses macromechanical analysis of both individual lamina and laminate materials; micromechanical analysis of lamina including elasticity based models; failure, analysis, and design of laminates; and a new chapter devoted to symmetrical and nonsymmetrical beams